Changes in anthropometric, biochemical, hematological, hormonal and cardiac markers in a group of late-adult amateur cyclists, after continuous and prolonged exercise on an uncontrolled diet - Maioli, Claudio; Di Dario, Marco; Lucianini, Rocco; Muzio, Fulvio; Cioni, Federico (Progress in Nutrition, 2019)
Purpose: to describe and compare the main biochemical and hematological parameters, markers of cardiac and stress suffering (cortisol), in an amateur group of 8 late-adult cyclists (average age 60.9 years s.d. 4.1 years) before and after a continuous bicycle course of 9 days with an actual duration of 7 days and a daily average of 103.5 Km (total of 725 km) on an uncontrolled diet. Results: body weight, BMI, systolic and diastolic pressure did not vary significantly in pre- and post-cycling performance (p> 0.05). There was no significant change in the pre- and post-red blood cell count in the hemochromocytometric hematological parameters (p = 0.57), while hemoglobin values decreased significantly after pedaling (p = 0.03), as did the average cellular hemoglobin values and the average cell concentration of hemoglobin (p = 0.002 and p = 0.0006, respectively). The number of platelets, white blood cells, the absolute number of neutrophils, lymphocytes, eosinophils, basophils and monocytes, and the percentage of neutrophils, eosinophilic lymphocytes, basophils and monocytes did not change significantly (p> 0.05). With regard to basic biochemistry, there was no significant variation in the values of glucose, urea, creatinine, alanine amino transferase, alkaline phosphatase, cholinesterase and creatinine kinase (p> 0.05). Aspartate amino transferase was found to be significantly greater after pedaling (p = 0.03). The values of albumin, total proteins, lactate dehydrogenase, total calcium, inorganic phosphorus, total magnesium, total iron, sodium and potassium were statistically non-significant between pre and post phases. The lipid profile, total cholesterol, triglycerides, lipases, HDL and LDL were also statistically non-significant even if HDL values increased on average after cycling performance (before 48.9 ± 9.5 and after 53.8 ± 12.4) while LDL values decreased on average (before 118.5 ± 28.8 and after 101.6 ± 10.3). In the hormone-labeling and vitamin group, ferritin was statistically non-significant. Pre and post changes in the stress hormone cortisol, PSA, vitamin B12 and natriuretic B-type NT-proBNP peptide were statistically non-significant. Instead, folate decreased significantly following the cycling performance (p = 0.017). In protein biochemistry, apolipoprotein A1 was statistically significant (p = 0.038) increasing after pedaling, while apolipoprotein B, C-reactive protein and transferrin were statistically non-significant. CK MB mass and troponin I in the cardiac markers did not undergo significant changes between pre and post phases. Conclusions: despite the small size of the chosen sample, parameters analyzed between pre and post continuous physical effort lead to the conclusion and confirmation of many data in the literature and, that is, that sporting activity conducted in an important way can improve the biochemical/functional state and, therefore, the health of practising subjects even in late adults and/or the elderly. This could postpone physical psychic decline caused by the natural progression of years.